A Biomechanical Review of the Squat Exercise: Implications for Clinical Practice - Rachel K Straub; Christopher M Powers (International Journal of Sports Physical Therapy)
The squat is one of the most frequently prescribed exercises in the rehabilitative setting. Performance of the squat can be modified by changing parameters such as stance width, foot rotation, trunk position, tibia position, and depth. An understanding of how the various squatting techniques can influence joint loading and muscular demands is important for the proper prescription of this exercise for various clinical conditions. The purpose of this clinical commentary is to discuss how the biomechanical demands of the squat can be influenced by various modifiable parameters. General recommendations for specific clinical conditions are presented.